Antimicrobial and antioxidant studies of Acacia mangium leaves extracts - Ismail, Che Aishah Nazariah; Abd. Samah, Othman (2010)
N-hexane, acetonitrile and methanol extracts of Acacia mangium leaves were screened for their antimicrobial and antioxidant activities. Disc diffusion assay has been done on four different concentrations of those extracts. Antioxidant activities of A. mangium leaves in all three extracts were screened qualitatively by rapid Thin Layer Chromatography (TLC) antioxidant assay. Yellow spots against purple 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) background were indicated in those three extract, followed by acetonitrile and the least in n-hexane extract. Lastly, total phenolic compound (TPC) assay was performed to investigate the content of total phenols (expresses as gram of gallic acid equivalents (GAE) per 100g of extract) and also to find its correlations with antimicrobial and antioxidant activities in the plant extracts. In this diffusion assay, the result has shown that only methanol extract exhibited inhibitory action against Escherichia coli while other microorganisms (Staphylococcus aureus, Streptococcus pyogenes, Salmonella typhimurium, Escherichia coli, Cryptococcus neoformans and Candida albicans) showed resistant action against all extracts. Methanol extract at 50,100,200 and 400, mg/ml concentration has exhibited diameter zone of inhibition of 7.33+-0.58mm, 8.5+-0.500mm, 10.0+-0.00mm and 11.0+-1.00mm against E.coli respectively. It was found that the inhibitory action of methanol extract was dose-dependent with MIC of more than 20mg/ml and no MBC detected. So, its inhibitory action was found to be bacteriostatic. For total phenolic compound assay, the increase the polarity of solvent for extraction, the higher the total phenolic content was found. The finding was indicated as methanol > acetonitrile > n-hexane extracts. Higher total phenol content in methanol extract (3.56g of gallic acid equivalent (GAE) per 100g of extract) has confirmed its association with both antimicrobial and antioxidant activities in this findings. Statistical analysis also revealed that there was a significant difference in types of extracts with both antimicrobial activity (p-value = 0.022) and total phenolic content (p-value = 0.027). It can be concluded that A. mangium leaves have weak antimicrobial activities but potent antioxidant activities and possess high total phenolic compounds.